Exploration Study of Cancer Hospital with Biophilic Design Approach in Bandarlampung - Suryo Bahwono Isyworo; Ai Siti Munawaroh; Tjetjeng Sofjan Surjana (Department of Architecture Universitas Muhammadiyah Jakarta, 2019)
Cancer, including the most dreaded disease. This is because the disease is still very difficult to cure and requires quite a long time in healing. This situation makes people with cancer experience severe depression. Therefore we need a cancer hospital design that can reduce the level of depression.The purpose of this research is want to perform design exploration studies cancer hospital by applying Biophilic architectural concept that is expected to reduce the level of depression.The methods used there are three, namely the study of literature, precedent studies and field studies.The results showed that the concept can be applied to the design biophilic in waiting room, inpatient unit and site. In the waiting romm there is a void leads directly to the pool below, wall coverings made of natural wood that seem deliberately not solid so sunlight can get into the room. Inpatient unit patients using a glass material that can be opened that serves to incorporate light and the natural air. Diguanakan color blue glass for the purpose of applying the color of sky and water. On the site can be seen when the patient enters the hospital neighborhood atmosphere to be conveyed to the patient is a natural setting so that the first impression when entering hospital patients do not think negative.